Os ensinos público e privado no Brasil e a incidência de sobre-educaç\~ao no mercado de trabalho - Maurício Cortez Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Overeducation refers to the extent to which workers acquired education levels in excess of that required by their jobs. Low educational level is pointed out as a determinant for the incidence of overeducation, which is usually associated with negative labor market outcomes. According to this argument, poorly educated workers are only qualified for jobs that require less years of schooling than they obtained. This paper aims to investigate the relationship between the probability of overeducation and the type of educational system (public or private education, which have quite different quality levels in Brazil). Estimates show that workers with secondary education who completed their study in public schools are more likely to be overeducated than those who completed their secondary education in private schools, which usually have better quality than the former ones. Among workers with a bachelor's degree, those who completed their programs in public institutions, which usually have better quality than private ones for higher education, are less likely to be overeducated.
Keywords: I21; J24; 330; private education; public education; overeducation